Effect of NaF, SnF2, and TiF4 Toothpastes on Bovine Enamel and Dentin Erosion-Abrasion In Vitro - Lívia Picchi Comar; Marina Franciscon Gomes; Naiana Ito; Priscila Aranda Salomão; Larissa Tercília Grizzo; Ana Carolina Magalhães (International Journal of Dentistry)
The aim of this study was to compare the effect of toothpastes containing TiF4, NaF, and SnF2 on tooth erosion-abrasion. Bovine enamel and dentin specimens were distributed into 10 groups (n=12): experimental placebo toothpaste (no F); NaF (1450 ppm F); TiF4 (1450 ppm F); SnF2 (1450 ppm F); SnF2 (1100 ppm F) + NaF (350 ppm F); TiF4 (1100 ppm F) + NaF (350 ppm F); commercial toothpaste Pro-Health (SnF2—1100 ppm F + NaF—350 ppm F, Oral B); commercial toothpaste Crest (NaF—1.500 ppm F, Procter & Gamble); abrasion without toothpaste and only erosion. The erosion was performed 4 × 90 s/day (Sprite Zero). The toothpastes’ slurries were applied and the specimens abraded using an electric toothbrush 2 × 15 s/day. Between the erosive and abrasive challenges, the specimens remained in artificial saliva. After 7 days, the tooth wear was evaluated using contact profilometry (μm). The experimental toothpastes with NaF, TiF4, SnF2, and Pro-Health showed a significant reduction in enamel wear (between 42% and 54%). Pro-Health also significantly reduced the dentin wear. The toothpastes with SnF2/NaF and TiF4/NaF showed the best results in the reduction of enamel wear (62–70%) as well as TiF4, SnF2, SnF2/NaF, and TiF4/NaF for dentin wear (64–79%) (P<0.05). Therefore, the experimental toothpastes containing both conventional and metal fluoride seem to be promising in reducing tooth wear.